Impact of a supervised training course on spirometry competency for primary care pediatricians. (3rd October 2021) - Ferrante, Giuliana; Licari, Amelia; Cilluffo, Giovanna; Lombardi, Enrico; Turchetta, Attilio; Pifferi, Massimo; Tancredi, Giancarlo; La Grutta, Stefania
Abstract: Objective: Spirometry is the most commonly performed lung function test, and performance, adherence to acceptability and repeatability criteria, and accurate interpretation of results help optimize the test's usefulness. This study aimed to measure the effects of spirometry training courses supported by the Italian Pediatric Respiratory Society (IPRS) on primary care pediatricians' (PCP) knowledge of spirometry test quality, ability to interpret results, and overall degree of satisfaction with the course. Methods: Of the six face-to-face courses, four lasted two days and two lasted one day: mean duration of theoretical lessons was five and four hours respectively; and practical sessions lasted eight and six hours, respectively. At the end of each course, participants took a learning test consisting of evaluating six flow-volume curves. Degree of satisfaction was assessed by asking participants to rank the relevance, quality, and usefulness of the course. Results: 261 PCPs were involved, with most (67.43%) taking two-day courses. Nearly all participants correctly identified normal and restrictive patterns. Intrathoracic large-airway obstruction was the pattern most difficult to identify correctly (70.5% overall), whereas > 80% of the participants correctly classified artifacts, obstructive-restrictive, and obstructive patterns. Participants in longer courses reported significantly higher values on the learning score. The overall degree of satisfaction average ranged between "good" and "excellent". Conclusions: This pilot study showed the greater impact of two-day courses than one-day courses for training PCPs to properly interpret spirometry, confirming that a practical module lasting at least six hours is sufficient to deliver adequate training on spirometry for healthcare professionals.